Health communication: mother's knowledge and treatment of fever in children - geby mora; Ria Setia Sari; Febi Ratnasari (INJECT (Interdisciplinary Journal of Communication), 2020)
Fever is in the first place of some of the most symptoms experienced by the child, the treatment of fever depends heavily on the role of parents especially the mother, The lack of knowledge possessed by the mother causes misperception of fever, this misperception results in inappropriate behavior in dealing with fever in the child then it is necessary to know further the level of maternal knowledge and treatment of fever in the child. This literature is to analyze journals on the level of maternal knowledge and the treatment of fever in children. The design of the research used in this study was literature review. This literature study through scientific publication search results with the range of 2015–2020 using the Research Gate, NCBI, Ebsco and Google Scholar databases.journals that correspond to the title and results of the synthesis matrix grouped into three parts namely input, process and output. Of the 20 articles analyzed entirely showed there is a link between maternal knowledge level and fever treatment in children, the average result of 45% of mothers with good knowledge level and 57.87% of mothers handling fever in children appropriately.